Analysis of Personal Protective Equipment in The Pandemic Period of Covid-19 on Medical Recording and Health Information Officers - Sri Nurcahyati; Sri Tanti Rahmayani; Lili Amaliah; Krisnita Dwi Jayanti; Septin Handayani (International Journal of Nursing Information, 2022)
One of the efforts to stop the transmission of Covid-19 to health workers is using masks, face shields, protective gowns, and gloves. PPE (Personal Protective Equipment) is vital to reduce the risks of contracting Covid-19. However, using complete PPE will significantly disrupt the process and way of working, especially when the availability of PPE is increasingly tricky during a pandemic. This study aimed to determine the factors that influence the use of personal protective equipment during the pandemic by medical record officer. The research method used was a quantitative observational analytic study using a cross-sectional design.  The sampling technique used a total sampling of 56 medical record officers in Kuningan, Indonesia. Data were obtained through interviews and observations. The study results of the factors that influence the use of personal protective equipment during a medical record officer's pandemic are knowledge of the use of PPE, attitudes and use of PPE, and availability of PPE with use. The information obtained in this study is that more and more medical record officers in hospitals are significantly at risk of Covid-19 transmission. Therefore medical record officers are expected to better protect themselves by using complete PPE when dealing with patients.